Biomass and nitrogen accumulation in white oat (Avena sativa L.) under water deficit - Prates Coelho, Anderson (Revista Ceres, 2025)
Knowledge on nitrogen absorption rate by crops can indicate important managements, especially the definition of rates of this nutrient and the best time for topdressing application. This study aimed to evaluate and compare the accumulation of biomass and nitrogen in white oat cultivated under severe, moderate and no water deficit. Treatments consisted of levels of irrigation, with four repetitions. The treatments under severe water deficit (L1), moderate deficit (L3) and no deficit (L5) received 11%, 60% and 100% of the water volume evapotranspired by the crop (ETc). For each treatment, six plants were collected in each replicate. After collection, plants were separated into leaves, culm and reproductive structures (panicle + grains). Second and third order regressions were tested to model the behavior of biomass and nitrogen accumulation in white oat leaves, culms, reproductive structures and total over time. The maximum total nitrogen accumulation in white oat plants in the treatments L1, L3 and L5 was 50 kg ha-1, 163 kg ha-1 and 246 kg ha1, respectively. Severe water deficit drastically reduced biomass and nitrogen accumulation in white oat. Severe water deficit causes earlier peak of biomass and nitrogen accumulation, reduces nitrogen accumulation rate and shortens cycle of white oats.